Interaction between tacrolimus and calcium channel blockers based on CYP3A5 genotype in Chinese renal transplant recipients - Zong, Huiying; Zhang, Yundi; Liu, Fengxi; Zhang, Xiaoming; Yang, Yilei; Cao, Xiaohong; Li, Yue; Li, Anan; Zhou, Penglin; Gao, Rui; Li, Yan (Frontiers in Pharmacology, 2024)
Abstract Objective: To investigate the effect of calcium channel blockers (CCBs) on tacrolimus blood concentrations in renal transplant recipients with different CYP3A5 genotypes. Methods: This retrospective cohort study included renal transplant recipients receiving tacrolimus-based immunosuppressive therapy with or without CCBs in combination. Patients were divided into combination and control groups based on whether or not they were combined with CCBs, and then further analyzed according to the type of CCBs (nifedipine/amlodipine/felodipine). Propensity score matching was conducted for the combination and the control groups using SPSS 22.0 software to reduce the impact of confounding factors. The effect of different CCBs on tacrolimus blood concentrations was evaluated, and subgroup analysis was performed according to the patients' CYP3A5 genotypes to explore the role of CYP3A5 genotypes in drug-drug interactions between tacrolimus and CCBs. Results: A total of 164 patients combined with CCBs were included in the combination groups. After propensity score matching, 83 patients with nifedipine were matched 1:1 with the control group, 63 patients with felodipine were matched 1:2 with 126 controls, and 18 patients with amlodipine were matched 1:3 with 54 controls. Compared with the controls, the three CCBs increased the dose-adjusted trough concentration (C0/D) levels of tacrolimus by 41.61 % to 45.57 % (P < 0.001). For both CYP3A5 expressers (CYP3A5*1*1 or CYP3A5*1*3) and non-expressers (CYP3A5*3*3), there were significant differences in tacrolimus C0/D between patients using felodipine/nifedipine and those without CCBs (P < 0.001). However, among CYP3A5 non-expressers, C0/D values of tacrolimus were significantly higher in patients combined with amlodipine compared to the controls (P = 0.001), while for CYP3A5 expressers, the difference in tacrolimus C0/D values between patients with amlodipine and without was not statistically significant (P = 0.065). Conclusion: CCBs (felodipine/nifedipine/amlodipine) can affect tacrolimus blood concentration levels by inhibiting its metabolism. The CYP3A5 genotype may play a role in the drug interaction between tacrolimus and amlodipine. Therefore, genetic testing for tacrolimus and therapeutic drug monitoring are needed when renal transplant recipients are concurrently using CCBs.